PENGARUH PENERAPAN METODE PEMBELAJARAN AKTIF TIPE COURSE REVIEW HOREY TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI MIA SMA PGRI 1 PADANG - Putra, Rian Nanda (Pendidikan Matematika, 2014)
This research is based on by studentâs comprehension in mathematical conceptswhic is low, the luack of studentâs responsibility in doing etercise and home work.The purpose of reseaich to know does the learning actife method Course ReviewHorey influence toword studentâs comprehension in mathematical concepts atgrade XI MIA SMA PGRI 1 Padang. This research is pre-eksperiment research,with one-shot case study. The population of this research is studentâs at class XIMIA SMA PGRI 1 Padang. The sampel is class XI MIA.3 that was takenrandomly. The instruments of research is quiz and pos-test like essay with testreliability is 0.34. Based on the description and data analysis above, it can beseen that studentâs comprehension in mathematical concepts get increase. Itshows that the arange of studentâs mathematical pos-test are 75,6. Therefore if itcompare with the standar score that is 75, so the average of studentâs pos-test arehigh than ideal score. In conclusion, learning active method Course ReviewHorey influence toword studentâs comprehension in mathematical concepts atgrade XI MIA SMA PGRI 1 Padang.